2020
DOI: 10.3758/s13414-020-02091-2
|View full text |Cite
|
Sign up to set email alerts
|

Paying attention to speech: The role of working memory capacity and professional experience

Abstract: Managing attention in multispeaker environments is a challenging feat that is critical for human performance. However, why some people are better than others in allocating attention appropriately remains highly unknown. Here, we investigated the contribution of two factors-working memory capacity (WMC) and professional experience-to performance on two different types of attention task: selective attention to one speaker and distributed attention among multiple concurrent speakers. We compared performance acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…To the best of our knowledge, previous studies have not directly addressed this inter-subject variance in attentional-bias, however several pervious papers that present individual-level data seem to exhibit similar variability (Ding and Simon 2012a, 2012b; Fuglsang et al 2017; Rosenkranz et al 2021). In the current data set, inter-subject variability in the magnitude of attentional bias was not correlated with working memory capacity (OSPAN), which sometimes drives individual differences in attentional abilities (Beaman et al 2007; Sörqvist and Rönnberg 2014a; Lambez et al 2020). Importantly, in our data, the overall speech-reconstruction accuracy was comparable in both sub-groups, indicating that the lack of attentional bias in some participants was not simply due to reduced signal to noise.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…To the best of our knowledge, previous studies have not directly addressed this inter-subject variance in attentional-bias, however several pervious papers that present individual-level data seem to exhibit similar variability (Ding and Simon 2012a, 2012b; Fuglsang et al 2017; Rosenkranz et al 2021). In the current data set, inter-subject variability in the magnitude of attentional bias was not correlated with working memory capacity (OSPAN), which sometimes drives individual differences in attentional abilities (Beaman et al 2007; Sörqvist and Rönnberg 2014a; Lambez et al 2020). Importantly, in our data, the overall speech-reconstruction accuracy was comparable in both sub-groups, indicating that the lack of attentional bias in some participants was not simply due to reduced signal to noise.…”
Section: Discussionmentioning
confidence: 70%
“…In comparison with Selective Attention, where there is a single focus of attention, Distributed Attention is a substantially more difficult task, that requires extensive top-down control for allocating limited linguistic processing resources among several stimuli (Treisman 1964; Duncan 1980; Koelewijn et al 2012; Bronkhorst 2015; Kawashima and Sato 2015; Mccloy and Lee 2015; Gagné et al 2017; Lambez et al 2020; Yuriko Santos Kawata et al 2020; Agmon et al 2021). The more taxing nature of Distributed Attention was confirmed by our behavioral results, which showed significantly reduced accuracy in answering questions about two concurrent narratives relative to one (in the Selective Attention condition).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they invite a more flexible account of the processing bottlenecks within the speech processing system, which takes into consideration the perceptual and cognitive load imposed by competing stimuli in a given context, in line with load theory of attention 88,90,[97][98][99] . As observed here, this allows for some degree of parallel processing of concurrent speech, at least under conditions where these loads are not excessively high, but are similar to those encountered in real-life 93 .…”
Section: Phrase-level Response To Task-irrelevant Speechmentioning
confidence: 63%
“…Supporting this perspective, others have also observed that the level of processing applied to task-irrelevant stimuli can be affected by task demands ( Hohlfeld and Sommer, 2005 ; Pulvermüller et al, 2008 ). Moreover, individual differences in attentional abilities, and particularly the ability to process concurrent speech, have been attributed partially to working-memory capacity, a trait associated with the availability of more cognitive resources ( Beaman et al, 2007 ; Forster and Lavie, 2008 ; Naveh-Benjamin et al, 2014 ; Lambez et al, 2020 ) but cf. ( Elliott and Briganti, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detecting the phrasal structure of task-irrelevant speech, while focusing primarily on processing the to-be-attended narratives, likely requires substantial working-memory for integrating chunks of information over time. Indeed, attention and working-memory are tightly linked constructs ( McNab and Klingberg, 2008 ; Gazzaley and Nobre, 2012 ; Vandierendonck, 2014 ), and as mentioned above, the ability to control and maintain attention is often associated with individual working-memory capacity ( Cowan et al, 2005 ; Beaman et al, 2007 ; Forster and Lavie, 2008 ; Naveh-Benjamin et al, 2014 ; Lambez et al, 2020 ). Therefore, one possible interpretation for the presence of a phrase-level response to task-irrelevant speech in the left posterior-parietal cortex and inferior frontal regions, is their role in forming and maintaining a representation of task-irrelevant stimuli in working-memory, perhaps as a means for monitoring the environment for potentially important events.…”
Section: Discussionmentioning
confidence: 99%